AL-QUR’AN DAN IDENTITAS (Menggali Makna Hijrah Sebagai Identitas Muslim Milenial Melalui Lintas Penafsiran) - Syamsuri, Syamsuri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
In this study, the researcher took the title "Al-Qur’an and Identity: Exploring the Meaning of Hijrah as a Millennial Muslim Identity Through Interpretation." The method used is contextual interpretation, initiated by Abdullah Saeed. This research concludes that the term "hijrah" has undergone a shift in meaning, namely that what was originally a territorial transfer has now become individual piety and is used as a person's Islamic identity, which is marked by a distinctive style of dress in the style of syar'i, lifestyle, and even style of speech. The term hijrah is interpreted as a change in all aspects of life by adopting the values contained in past hijrah events, namely changes towards a stronger faith and changes in social, national, and state structures. In the Indonesian millennial context, hijrah becomes the identity of a true Muslim. This is an opportunity as well as a challenge for Muslims today. The challenge is that the measure of one's Islam is only seen in its outward aspect or appearance. Meanwhile, Islam also places great emphasis on aspects of universal and substantial values in every dimension of its teachings.